Teachers’ Perspectives on Innovative and Interactive Teaching Methods: Perspective of Mobile Learning - Latifi, Fadil; Kasumi, Hysen (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This study aims to reflect teachers' perspectives on the use of innovative and interactive teaching methods (mobile learning and others) and to present the importance of the application of modern teaching methods by first-level teachers (grades 1-5) and second-level teachers (grades 6-9), in the development of student competencies. The research includes the Anamorava Region in Kosovo which covers an area of ​​650 km2 and has about 200,000 inhabitants. Quantitative methods were used to research this issue, while Likert scale questionnaires were used as a tool for measuring teachers' thoughts and attitudes. The research sample consists of 97 teachers working with first and second-level students. The results show that teachers do not use a variety of methods while a number of them state that teaching methods are always in coherence with the age and skills of students. A small number of teachers pay special attention to students' prior knowledge. Based on the general data from the research, I have noticed that teachers do not practice enough modern teaching methods to develop students' competencies and promote their activity and creativity.